A Mutation in Plasma Platelet-activating Factor Acetylhydrolase (Val279Phe) Is a Genetic Risk Factor for Cerebral Hemorrhage but not for Hypertension - Yoshida, Hidemi; Imaizumi, Tadaatsu; Fujimoto, Koji; Itaya, Hiroyuki; Hiramoto, Makoto; Yoshimizu, Nobuhiro; Fukushi, Kazue; Satoh, Kei (Thrombosis and Haemostasis, 1998)
Platelet-activating factor (PAF) acetylhydrolase is an enzyme that inactivates PAF. Deficiency of this enzyme is caused by a missense mutation in the gene. We previously found a higher prevalence of this mutation in patients with ischemic stroke. This fact suggests that the mutation might enhance the risk for stroke through its association with hypertension. We have addressed this hypothesis by analyzing the prevalence of the mutation in hypertension. We studied 138 patients with essential hypertension, 99 patients with brain hemorrhage, and 270 healthy controls. Genomic DNA was analyzed for the mutant allele by the polymerase-chain reaction. The prevalence of the mutation was 29.3% (27.4% heterozygotes and 1.9% homozygotes) in controls and 36.2% in hypertensives and the difference was not significant. The prevalence in patients with brain hemorrhage was significantly higher than the control: 32.6% heterozygotes and 6.1% homozygotes (p <0.05). PAF acetylhydrolase deficiency may be a genetic risk factor for vascular diseases.